The Corporate Saving Glut and Falloff of Investment Spending in OECD Economies. Issue Volume 64:Issues 4(2016) (November 2016) - Gruber, Joseph; Kamin, Steven
Abstract We explore the increase in the net lending of non-financial corporations across the OECD following the global financial crisis. We document that this rise reflects both increases in saving and declines in investment. Panel regressions reveal that the fall in investment across OECD economies was generally in line with fundamentals—GDP growth, interest rates, and profits—though in some countries the weakness was more pronounced. We find little evidence that firms were reducing investment to strengthen their balance sheets, as payments to shareholders remained strong and were uncorrelated with investment. We conclude that, at least from the investment side, the rise in corporate net lending probably does not reflect a shift in corporate behavior relative to past norms.